Risk factors for prostate cancer: a case-control study investigating selected key exposures and their interactions with predisposition genes - Rahman, Aneela Atta Ur (2010)
Prostate cancer is the UK number one male cancer. Evidence from epidemiological studies suggests only age, race and family history as established risk factors. Other factors such as low dose diagnostic radiations and surrogate hormone markers such as baldness, finger length pattern and acne are hypothesized to have a potential role in the aetiology of prostate cancer. It is evident that genetics plays an important role in prostate cancer aetiology.